Domestic Dynamics on Foreign Policy: India's Withdrawal from Regional Comprehensive Partnership Agreement (RCEP) Negotiations - Noudy Naufal (Universitas Airlangga, 2021)
India’s decision to withdraw from Regional Comprehensive Economic Partnership (RCEP) has been one of the shocking event in the development of international trade. Not only obstructing many regionalist agenda between India and the whole of Asia-Pacific region, this decision is considered to be in the exact opposite of India’s attempts to direct its foreign policy towards its eastern neighbours, especially on the East and Southeast Asia, through India’s participations in several free trade agreements. This thesis will attempt to explain India’s withdrawal from RCEP negotiation by looking at domestic factors. It argues that domestic pressures are the main factors for India to withdraw from RCEP’s negotiation rounds. In this research, the author will use conceptual framework developed by Thomas Risse-Kappen to classify the influences of domestic actors on foreign policy of a country based on its political system and societal groups to understand more the influences of domestic actors to Indian foreign policy. This research also shows that apart from domestic stakeholders perceptions that the country’s membership in the RCEP doesn’t benefit their economic interests, huge pressures came especially from Hindu nationalist groups, especially from Rashtriya Swayamsevak Sangh (RSS), as the core mass support of the current government’s party under the premiership of Narendra Modi (Bharatiya Janata Party – BJP), has been one of the major domestic pressures to understand the roots on India’s withdrawal from RCEP’s negotiation rounds.